COMPORTAMENTO FISIOLÓGICO DE NOVILHAS PANTANEIRA E GIROLANDO NAS DIFERENTES ESTAÇÕES DO ANO - LIMA, P. G. L.; LIMA, A. C. B.; SANTOS, M. G. R.; MARTINEZ, D. V. S.; SALLA, L. E.; OLIVEIRA, M. V. M. (ANAIS DO ENIC, 2016)
-